2022
DOI: 10.1111/cid.13136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the distribution characteristics of the mandibular lingual foramen and its potential risks during implant surgery using cone‐beam computed tomography a cross‐sectional, retrospective study

Abstract: Objectives The lingual foramen is a risk factor for implantation and other mandibular surgeries, but there are few systematic studies on the anatomical and distribution characteristics of the lingual foramen in the entire mandible. Materials and Methods A retrospective study was performed using 405 CBCT images. The anatomical characteristics and symmetrical distribution of the mandibular lingual foramen were analyzed. Results All patients had at least one lingual foramina. According to the positional relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In another study in the literature, similar to the results of our study, it was reported that LFs were most commonly localized in the midline region, with an incidence of 55.8% [21].…”
Section: Discussionsupporting
confidence: 91%
“…In another study in the literature, similar to the results of our study, it was reported that LFs were most commonly localized in the midline region, with an incidence of 55.8% [21].…”
Section: Discussionsupporting
confidence: 91%